A centralised control mechanism for network resource allocation in grid applications. (16th January 2009) - Reinhard, Vincent; Tomasik, Joanna
In a high-speed network, application-network interactions are considerations of paramount importance for service responsiveness. The CARRIOCAS project aims to study the high-speed networking features that are needed to support distributed applications in an operator network. These features will be implemented later. The proposed architectural solutions will be validated in a pilot network used as a grid infrastructure for distributed applications. This network will be a part of the CARRIOCAS project outcome. We propose a mechanism for the introduction of application data in the network with respect to CARRIOCAS architecture. Using simulations, we study the system performance for applications that demand the quality of service in terms of latency and data loss. Our results show that a centralised control of application-network applications is efficient for small and fast networks.